Jaminan Kerahasiaan Informasi Pajak Atas Harta Benda Wajib Pajak Dalam Pemeriksaan Pengelolaan dan Tanggung Jawab Keuangan Negara Yang Dijalankan Badan Pemeriksa Keuangan - Johannes Johny Koynja (Fakultas Hukum Universitas Mataram, 2016)
This study departs from the legal issues that were born from the conflict of two interests are equally protected by the constitution, namely: First, the interest in the form of the constitutional rights of the taxpayer on his property, in this case the guarantee of confidentiality is protected by law on all the information that has been given to the state (tax authorities) in respect of its obligations to pay taxes according to the principle of self-assessment; Secondly, the benefit in the form of constitutional authority of Audit Board of the Republic of Indonesia (BPK) to audit state finances freely and independently. There are two questions of urgency in the research related to the conflict norm constitutional authority of Audit Board of the Republic of Indonesia (BPK) to information on property tax taxpayer, namely: First, where was the norm conflicts related to the constitutional authority of the Supreme Audit Agency (BPK) to get property tax on the Taxpayer? Second, how real implementation Taxpayer confidentiality to information on property tax Taxpayer with the implementation of self assessment system in the Indonesian tax system? egislation governing state finances, namely the Act Number 17 of 2003 on State Finance and the Act Number 15 of 2004 concerning Management and Accountability of State Finance, and the Act Number 15 of 2006 regarding the Supreme Audit Agency (BPK) has placed the Supreme Audit Agency (BPK) as a body that tends to monopoly the inspections on state finances, in addition to creating instability in the taxation sector.